2006
DOI: 10.1007/s11864-006-0030-9
|View full text |Cite
|
Sign up to set email alerts
|

Second- and third-line treatments in non-small cell lung cancer

Abstract: Slow but steady progress has been made in the treatment of advanced non-small cell lung cancer. For first-line therapy, multiple chemotherapy combination therapies can extend survival and improve quality of life. And recently, for the first time ever, a noncytotoxic agent, the antivascular endothelial growth factor antibody bevacizumab, has been shown to improve survival when added to chemotherapy. Striking improvements have also been made in second-line treatment. In August 2004, only one agent was US Food an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…According to published data, docetaxel, pemetrexed and the epidermal growth receptor (EGFR) tyrosine kinase inhibitors (TKIs) erlotinib and gefitinib are all acceptable choices for third-line therapy [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Unfortunately, the clinical benefit deriving from third-line treatments is often limited to a small proportion of the patients treated, whereas it is not uncommon to observe toxic sideeffects with lack of efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…According to published data, docetaxel, pemetrexed and the epidermal growth receptor (EGFR) tyrosine kinase inhibitors (TKIs) erlotinib and gefitinib are all acceptable choices for third-line therapy [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Unfortunately, the clinical benefit deriving from third-line treatments is often limited to a small proportion of the patients treated, whereas it is not uncommon to observe toxic sideeffects with lack of efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Using cisplatin (27)(28)(29) and Dtxl (30)(31)(32)(33)(34)(35), two widely used Food and Drug Administrationapproved chemotherapeutics with different solubility profiles, and prostate cancer as a model disease, we demonstrate targeted drug delivery to PSMA-expressing cells. First, a functionalizedpoly(lactic acid) (PLA) polymer was synthesized and derivatized with platinum(IV) [Pt(IV)] prodrug pendants which, after reduction, release cisplatin.…”
mentioning
confidence: 99%
“…The authors quated like candidates for third-line chemotherapy: single-agent gemcitabine, irinotecan, and oral topotecan [8]. The study published by Song et al was a retrospective study which confirmed the small but proved benefit of third-line chemotherapy.treated with doublet of cytostatics, 2.80 months for single-agent and 2.97 months for EGFR-TKIs arms (P=0.033) [9].…”
Section: Discussionmentioning
confidence: 94%